VD_FINDINFO Décision / 2013 / 225 vom 15. März 2013 - VD Tribunal cantonal (2013)
DÉCISION SUR FRAIS, DÉPENS | 69 al. 1bis LAI, 61 let. a LPGA, 61 let. g LPGA, 49 al. 1 LPA-VD, 55 al. 1 LPA-VD, 94 al. 1 let. a LPA-VD